PENGARUH BEBERAPA INSEKTISIDA TERHADAP HAMA Lamprosema indicata F. DAN Spodoptera litura F. PADA TANAMAN KEDELAI (Glycine max (L) MERRIL.) - Rotua Maryance Gultom; Yuswani Pangestiningsih; Lahmuddin Lubis (Universitas Sumatera Utara, 2014)
Rotua Maryance Gultom, “The Influenced some Insecticide on Soybean (Glycine max (L) Merril.)Pest Lamprosema indicata F. and Spodoptera litura F. in the field”. The objectives of the researchwere to study the effect of some Insecticide to Soybean (Glycine max (L) Merril.) pest Lamprosemaindicata F. dan Spodoptera litura F. The research was held at Telaga Sari Village, DevelopmentTanjung Morawa, Medan, North Sumatera from July until September 2013. The method used NonFactorial Randomized Group Design, consist of 7 treatments and 3 repetable that is control, papayaseed, indian mulberry seed seed, mahogany seed, Bacillus thuringiensis, Beauveriabassiana, and dimetoat. The results showed that the observated in 43 days after growth, dimetoatinsecticide and papaya seed insecticide effectived aplicable to Lamprosema indicata F. (12.98%)and (23.37%), with total larvae 1.34 dan 1.44. but for Spodoptera litura F. mahogany seedinsecticide is effectived (29.42%).Keywords : Soybean, Lamprosema indicata, Spodoptera litura